Decreasing Social Inequities through Decentralization : Morocco Social Priorities 1-Health Project - Kuehnast, Kathleen (World Bank, Washington, DC, 2012)
The Morocco Social Priorities Program incorporates three complementary projects, one of which is the Basic Health Project. These projects are being implemented simultaneously in the 14 poorest provinces, in which 27 percent of the total population and 43 percent of the rural population live. The overall objectives of the Social Priorities Project are to assist the government to implement its strategy to increase access of the poor to basic social services, enhance social protection, and create new opportunities for the poor to participate in economically productive activities. Social Development best practices were recognized as: the multi-dimensional approach to poverty reduction aimed at enhancing opportunities, capabilities, empowerment, and security of the poor; Participatory processes in implementation; organizational and institutional decentralization; and ongoing monitoring and evaluation of social development outcomes by the government and community.